Konsep Manajemen Mutu Terpadu Dalam Pendidikan - Hairiyah . (Universitas Alma Ata, 2015)
Abstrak Total quality Management (TQM) as a management tips that focus on process improvement of customer satisfaction, which is deemed successful in the industrialized world began to demand institutions to be adapted with the aim of producing a “product” of quality. In the perspective of education MMT is an organization that provides services and products in the form of (service ). Every individual in an organization that is implementing (TQM) is a manager in any sphere of competence. In the context of education, the improvement is not only done by the government but also carried out by the staff of the administration by the improvement of the system and the culture of administrative services, and also by teachers with the learning process improvement. Thus, students are regarded as one of the customers will be able to feel satisfaction in the service of the institution. Keywords: Continuous improvement, total involvement, customer satisfaction